Which factor matters for financial crises: leverage level or leverage growth?. Issue 13 (28th July 2020) - Bian, Wenlong; Ge, Tingting; Ji, Yang
ABSTRACT: Prior studies have shown a significant impact of the leverage level on economic outcomes. This study extends the literature by examining the role of leverage growth in predicting the occurrence of financial crises. Based on a dataset of 42 economies over the period 1980–2017, the results indicate a positive and significant association between leverage growth and the likelihood of financial crises. Moreover, leverage level plays no relevant role in predicting the financial crises after leverage growth has been controlled for. Further analysis also confirms the contribution of relative sectoral leverage growth to financial crises. Specifically, both the difference between the private and the government leverage growth, and the difference between the household and non-financial corporate leverage growth are positively associated with the likelihood of financial crises. These findings suggest that we should pay much more attention to leverage growth and its impacts on financial crises.